Liquid li structure and dynamics: A comparison between OFDFT and second nearest‐neighbor embedded‐atom method. Issue 9 (8th April 2015) - Chen, Mohan; Vella, Joseph R.; Panagiotopoulos, Athanassios Z.; Debenedetti, Pablo G.; Stillinger, Frank H.; Carter, Emily A.
<x xml:space="preserve">Abstract</x> The structure and dynamics of liquid lithium are studied using two simulation methods: orbital‐free (OF) first‐principles molecular dynamics (MD), which employs OF density functional theory (DFT), and classical MD utilizing a second nearest‐neighbor embedded‐atom method potential. The properties studied include the dynamic structure factor, the self‐diffusion coefficient, the dispersion relation, the viscosity, and the bond angle distribution function. Simulation results were compared to available experimental data when possible. Each method has distinct advantages and disadvantages. For example, OFDFT gives better agreement with experimental dynamic structure factors, yet is more computationally demanding than classical simulations. Classical simulations can access a broader temperature range and longer time scales. The combination of first‐principles and classical simulations is a powerful tool for studying properties of liquid lithium. © 2015 American Institute of Chemical Engineers AIChE J, 61: 2841–2853, 2015